2023
DOI: 10.32604/cmes.2022.023195
|View full text |Cite
|
Sign up to set email alerts
|

An Interpretable CNN for the Segmentation of the Left Ventricle in Cardiac MRI by Real-Time Visualization

Abstract: The interpretability of deep learning models has emerged as a compelling area in artificial intelligence research. The safety criteria for medical imaging are highly stringent, and models are required for an explanation. However, existing convolutional neural network solutions for left ventricular segmentation are viewed in terms of inputs and outputs. Thus, the interpretability of CNNs has come into the spotlight. Since medical imaging data are limited, many methods to fine-tune medical imaging models that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The authors employed grabcut technique with K-means clustering for enhancing the segmentation of CT scan images for various parts and deep learning techniques were used for detection of disease [39]. Authors suggested performing global average pooling, replacing the fully connected layer of the neural network to improvise the feature selection process, hence the image pre-processing procedure can be improved [40].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors employed grabcut technique with K-means clustering for enhancing the segmentation of CT scan images for various parts and deep learning techniques were used for detection of disease [39]. Authors suggested performing global average pooling, replacing the fully connected layer of the neural network to improvise the feature selection process, hence the image pre-processing procedure can be improved [40].…”
Section: Literature Reviewmentioning
confidence: 99%